Reducing Accounting Fraud Tendencies: The Role of Internal Control Effectiveness, Information Asymmetry, and Religiosity - I Nyoman Arta Nadi; Luh Kade Datrini (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2026)
Purpose – This study aims to examine the effect of internal control effectiveness, information asymmetry, and religiosity on the tendency of accounting fraud in Village Credit Institutions (LPD) in Baturiti District. Methodology/approach – This research employed a quantitative approach using primary data collected through questionnaires distributed to LPD management and employees directly involved in financial management. The population consisted of 139 individuals, with 107 respondents selected through purposive sampling. Data were analyzed using multiple linear regression techniques. Findings – The results indicate that internal control effectiveness has a negative and significant effect on the tendency of accounting fraud, while information asymmetry has a positive and significant effect. Religiosity also shows a negative and significant influence on the tendency of accounting fraud. These findings suggest that stronger internal controls and higher religiosity reduce fraud tendencies, whereas greater information asymmetry increases the likelihood of fraud. Novelty/value – This study provides empirical evidence on the combined role of organizational control systems, information transparency, and moral values in preventing accounting fraud within LPDs. The results can serve as a reference for improving governance and fraud prevention strategies in rural financial institutions. Keywords: Internal Control Effectiveness, Information Asymmetry, Religiosity, Accounting Fraud Tendency, Village Credit Institutions (LPD)